Longitudinal and Regional Trends in Paramedic Student Exposure to Advanced Airway Placement: 2001–2011. (1st July 2013) - Westgard, Bjorn C.; Peterson, Bjorn K.; Salzman, Joshua G.; Anderson, Richard; Buldra, Mike; Burnett, Aaron M.
Abstract Objectives. The primary aims of this study were to determine whether the frequency of placement, type of advanced airway, and settings of advanced airway placement (clinical vs. field) have changed for paramedic students over the last 11 years, and to describe regional differences regarding the same set of variables. Methods. This study was a retrospective review of prospectively reported airway procedures documented by paramedic students in Fisdap (http://www.fisdap.net). Students were included if they graduated from a paramedic program, had procedure entries verified by a preceptor, and provided consent for research. Exclusion criteria included students who had a total number of airway placements ≥2 standard deviations from the mean or had 0 airway placements recorded, and programs with <10 graduating students total over the study period. Airway device types and educational settings were descriptively compared over the 11-year study period by year and region. Results. A total of 8, 934 paramedic student records were reviewed, with 2, 811 excluded based on a priori criteria, leaving 6, 123 records for analysis. In each year, the median number of airway devices placed per student was greater in the clinical setting. Endotracheal intubation (ETI) was more common than alternative airway placement in both the field and clinical settings. The median number of clinical ETIs per student has remained relatively constant at 7. The median number of field ETIs per student ranged from 0 to 1 over the study period, with a median alternative airway placement rate of 0 for both clinical and field settings. For all regions, the majority of procedures were performed in a clinical environment. The median number of clinical alternative airway device placements was 0 for all regions. The number of clinical ETIs ranged from 5 to 11 per student, with the highest number of ETIs per student in the West North Central and New England regions and the lowest in the West South Central and East South Central regions. Conclusion. Paramedic students gain the majority of their advanced airway experience in the clinical setting. ETI remains more common than alternative airway placement, although there is significant geographic variation in the number of ETIs per student. High rates of clinical intubations do not correlate with high rates of field intubations.